An assessment of the local residents’ perceptions on the socioeconomic impact of Iskandar Malaysia - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah (School of Humanities, Universiti Sains Malaysia, 2016)

(untitled)
This paper discusses the perceptions of the local residents on the socio-economic changes of Iskandar Malaysia. The study investigates the local people’s knowledge and perception towards Iskandar Malaysia development as one of the main economic accelerators in the southern part of Peninsular Malaysia. A survey involving semi-structured questionnaire on 916 respondents was carried out among the local people within Iskandar Malaysia and interviews with the local authorities and stakeholders were also conducted to assess their perceptions toward the development. Results from the study revealed that the majority of the respondents lacked the necessary awareness and avenue to participate in the Iskandar Malaysia’s decision making process. The findings of the study showed that the new regional development area is under Malaysian government’s directive and used complete top-down approach in its implementation approach.